“I AM THOR/DUST DAHO”: mnemonic devices used by the Paris Fire Brigade to teach initial measures in undertaking a CBRN event - Giaume, Louise; Daniel, Yann; Calamai, Franck; Derkenne, Clément; Kedzierewicz, Romain; Demeny, Aude; Bertho, Kilian; Travers, Stéphane; Prunet, Bertrand; Dorandeu, Fréderic (Critical care (London, England), 2021)
Despite the indisputable, constant threat of real CBRN situations, fortunately, they are rare. [...]most first responders have never been exposed to real CBRN situations. [...]first responders often have insufficient levels of training and knowledge, and few have the opportunity to attend CBRN training refresher courses or simulation courses [2]. The dissemination of the TCCC approach, and its equivalents, among modern warfare personnel has improved the probability that individuals with war-related injuries will arrive alive to the hospital [15]. [...]based on this approach, we developed a French mnemonic device to make the CBRN-CS easier to remember. Blacker SD, Carter JM, Wilkinson DM, Richmond VL, Rayson MP, Peattie M. Physiological responses of Police Officers during job simulations wearing chemical, biological, radiological and nuclear personal protective equipment.